Intraspecific variability of dihydrochalcone, chromenes and benzoic acid derivatives in leaves of Piper aduncum L. (Piperaceae) - Morandim, Andreia de Araújo; Kato, Massuo Jorge; Cavalheiro, Alberto José [UNESP]; Furlan, Maysa [UNESP] (My University, 2009)
Chemical analysis carried out in leaves of 18 specimens of Piper aduncum L. (Piperaceae) occurring at Ripasa Reserve, Araraquara, SP, Brazil indicated two distinct populations when investigated over a period of 14 months (January 2000 to February 2001) and then submitted to cluster analysis. The two groups were characterized by accumulation of prenylated benzoic acids, chromenes and dihydrochalcone, respectively. A total of seven compounds were identified by HPLC analysis and compared with standards including two prenylated benzoic acid [aduncumene (1) and 3-(3′-7′-dimethyl-2′-6′-octadienyl)- 4-methoxy-benzoic acid (5)], four chromenes [methyl 2,2-dimethyl-8-(3′- methyl-2′-butenyl)-2H-1-chromene-6-carboxylate (4), methyl 2,2-dimethyl-2H-1-chromene-6-carboxylate (2b), methyl 8-hydroxy-2,2-dimethyl-2H- 1-chromene-6-carboxylate (3) and 2,2-dimethyl-2H-1-chromene-6-carboxylic acid (2a)] and one dihydrochalcone [2′,6′-dihydroxy-4′-methoxy- dihydrochalcone (6)]. © 2009 Academic Journals.
Keywords: Chemotypes and HPLC analysis; Instraspecific variability; Piper aduncum; 2',6' dihydroxy 4' methoxy dihydrochalcone; 2,2 dimethyl 2h 1 chromene 6 carboxylic acid; 3 (3' 7' dimethy 2' 6' octadienyl) 4 methoxy benzoic acid; aduncumene; methyl 2,2 dimethyl 2h 1 chromene 6 carboxylate; methyl 2,2 dimethyl 8 (3' methyl 2' butenyl) 2h 1 chromene 6 carboxylate; methyl 8 hydroxy 2,2 dimethyl 2h 1 chromene 6 carboxylate; Piper aduncum extract; plant extract; unclassified drug; drug structure; high performance liquid chromatography; Piperaceae; plant leaf; quantitative analysis